Infected Hydrocele of the Canal of Nuck - Parkash Mandhan; Zaid Raouf; Khalid Bhatti (Case Reports in Urology)
Hydrocele of the canal of Nuck in children is rare. It may present as incarcerated inguinal hernia and necessitates emergency exploration. Risk of infection in hydrocele of the canal of nuck is very rare. We present a case report of a 5-year-old girl who presented with a left tender inguinolabial region swelling with fever, tachycardia, and mild dehydration. The clinical features were suggestive of strangulated left inguinal hernia and further imaging and surgical exploration revealed it to be an infected hydrocele of the canal of Nuck. High ligation and hydrocelectomy were performed. Hydrocele of the canal of Nuck in a female child presenting with an inguinal swelling should be considered in differential diagnosis.